Diagnostic utility of fine needle aspiration cytology in thyroid lesions - Manzoor, Farzana; Sheikh, Arif R.; Sheikh, Bilal A. (International Journal of Research in Medical Sciences, 2020)
Background: Thyroid fine needle aspiration cytology (FNAC) is an important screening tool and thereby dictates clinical management. The exclusion of non-invasive follicular variant of papillary carcinoma (NIFVPTC) from thyroid malignancies and its reclassification as non-malignant entity i.e., non-invasive follicular thyroid neoplasm with papillary like nuclear features (NIFTP) has added a new dimension. Aim of this study was to study the role of fine needle aspiration cytology in screening thyroid lesions by correlation with histopathological examination and to calculate diagnostic accuracy of FNAC considering NIFTP as non-malignant and compare it with pre NIFTP era. Methods: It was an observational study done over a period of 2 years (2017-2018). It included the cases where FNAC was followed subsequently by histopathology. FNAC results were correlated with histopathological diagnosis established thereof. Results: A total of 107 patients were included in this study. Considering NIFTP as non-malignant, sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were 92.97%, 100%, 100%, 92.73% and 96.23% respectively, that is significantly higher if authors considered NIFTP as malignant. Conclusions: FNAC plays an indispensable role in making preliminary diagnosis in thyroid lesions. There is a notable increase in diagnostic accuracy of FNAC in thyroid lesions and significant decrease in risk of malignancy by considering NIFTP as non-malignant.